2022
DOI: 10.3390/antibiotics11040517
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Doses of Ceftolozane/Tazobactam as Monotherapy or in Combination with Amikacin to Treat Carbapenem-Resistant Pseudomonas aeruginosa

Abstract: Carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a hospital-acquired pathogen with a high mortality rate and limited treatment options. We investigated the activity of ceftolozane/tazobactam (C/T) and its synergistic effects with amikacin to extend the range of optimal therapeutic choices with appropriate doses. The E-test method is used to determine in vitro activity. The optimal dosing regimens to achieve a probability of target attainment (PTA) and a cumulative fraction of response (CFR) of ≥90% were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Another study aiming to optimize C/T dosing for the treatment of CRPA found that only the combination of C/T with amikacin as a loading dose of 20–25 mg/kg followed by 10–15 mg/kg/day achieved a cumulative fraction of response of >90% [ 103 ]. It should also be noted that critically ill patients who need renal replacement therapy may require higher dosing regimens to maintain effective serum concentrations [ 104 ].…”
Section: Key Factors Related To Therapymentioning
confidence: 99%
“…Another study aiming to optimize C/T dosing for the treatment of CRPA found that only the combination of C/T with amikacin as a loading dose of 20–25 mg/kg followed by 10–15 mg/kg/day achieved a cumulative fraction of response of >90% [ 103 ]. It should also be noted that critically ill patients who need renal replacement therapy may require higher dosing regimens to maintain effective serum concentrations [ 104 ].…”
Section: Key Factors Related To Therapymentioning
confidence: 99%
“…The increasing emergence of multi-drug-resistant P. aeruginosa and K. pneumoniae strains limits the treatment options, which increases the morbidity and mortality of patients [ 7 ]. This situation enforces the search and more frequent application of new drugs such as ceftolozane–tazobactam, new drug combinations, or new applications of commonly known antimicrobials [ 3 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%